Adaptive Potential of Young People as a Factor af Mental Health-Preserving - Lytvynenko, Olga; Zlatova, Liudmyla; Zasenko, Vіacheslav; Prokhorenko, Lesya; Lunov, Vitalii (Journal of History Culture and Art Research, 2020)
The adaptive potential of a person in the range of his socio-psychological resources represents a vital problem, which is challenging from the perspective of the society’s demands and in specifying certain methodologies of social psychology. The adaptive potential is now represented in researches as a certain combination of constitutional-morphological, physiological, bioenergetic, neurodynamic, psychic, psychological and other properties of a person. It is noted that the corresponding properties determine the ability of a person to adapt to certain activities and to the natural and social environment. It should be mentioned, that the transformational processes in the modern social environment require the actualization of the personal potential in the way appropriate to its challenges, which in the first instance draws the attention of researchers and experts in social work to the modern youth both on the level of the scientific generalization and socio-psychological support. Thus, the main attention is given to the socio-psychological context of the problem explored. The important line of the problem under exploration is related to the study of the adaptive potential in one’s system of resources as a factor of preserving one’s psychological health.